2011
DOI: 10.5897/ajmr11.218
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological analysis of drinking water sources

Abstract: The quality of potable water and treatment of waterborne diseases are critical public health issues. Bacterial contamination of drinking water sources is the most common health risk. The research determines bacteriological quality of drinking water sources in Serbo town, south west Ethiopia. A Cross-sectional study design on bacteriological analysis of drinking water was conducted in Serbo town from September to October, 2010. 100 ml of water specimen was collected from each water sources and transported for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…Results of this study were in agreement with the reported detection of coliforms from 75 % of unprotected well and spring samples from North-Gondar, Ethiopia [ 29 ] and the 90 % detection of the same microbial groups from protected spring samples of Uganda [ 30 ]. Similarly, 87.5 % of the water samples collected from other six protected wells and eighteen unprotected wells of Serbo town [ 31 ] revealed TTC count above the permissible limits for drinking water.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study were in agreement with the reported detection of coliforms from 75 % of unprotected well and spring samples from North-Gondar, Ethiopia [ 29 ] and the 90 % detection of the same microbial groups from protected spring samples of Uganda [ 30 ]. Similarly, 87.5 % of the water samples collected from other six protected wells and eighteen unprotected wells of Serbo town [ 31 ] revealed TTC count above the permissible limits for drinking water.…”
Section: Discussionmentioning
confidence: 99%
“…e variation might be the protected springs are continuously openly flowed and easy to wash. is is also supported by a finding from Farta woreda [14]. e study in Serbo town, southwest Ethiopia, showed that fifty percent had faecal coliforms, of these 35.7% had E. coli [19]. e contamination of these water sources might be due to poor source protections.…”
Section: Discussionmentioning
confidence: 65%
“…Although more attention is being directed to understand the microbial challenges experienced by Addis Ababa's drinking water, few studies use culture-independent methods. For example, several studies on the quality of drinking water in various regions across Ethiopia and in Addis Ababa used culture-dependent techniques focusing on speci c indicator organisms [13][14][15]. Despite their convenience for routine monitoring, culture-based methods tend to underestimate the diversity and potential presence of both opportunistic and pathogenic microorganisms due to poor cultivability [16] or growth competition by nonpathogenic heterotrophic plate count (HPC) bacteria [17].…”
Section: Introductionmentioning
confidence: 99%